Effect of denture soft liner on mandibular ridge resorption in complete denture wearers after 6 and 12 months of denture insertion: A prospective randomized clinical study - B Dinesh Babu; Veena Jain; Gunjan Pruthi; Nidhi Mangtani; Rajath S Pillai (Wolters Kluwer Medknow Publications, 2017)
Purpose: Soft liners act as a cushion between the denture base and the residual ridge. Hence, it is important to study their effect on resorption of mandibular denture bearing area. Therefore, the purpose of this study was to evaluate the influence of soft denture liner on mandibular ridge resorption after 1 year in completely denture wearers. Materials and Methods: Twenty-eight completely edentulous patients having age between 45 and 60 years with well-formed ridges in class I jaw relations were selected as per the inclusion and exclusion criterion. Randomization chart was used to enroll participants in experimental and control groups who were given mandibular dentures with and without soft denture liner, respectively. Vertical measurements were made on orthopantomograph and analyzed using Adobe Photoshop 7.0 software at five points, i.e., one at central incisor and two points at right and left first premolars and two in each first molar region. Results: On application of repeated measures analysis of variance, both groups showed a significant change in bone height after denture delivery (P < 0.05). Intergroup comparison (Wilcoxon rank sum test) of bone height in different regions at various time intervals showed statistically significant difference in bone levels (P < 0.05) from baseline to 6 months and baseline to 12months (P < 0.01), while the difference was statistically not significant during 6 and 12 months' period. Conclusion: The use of soft denture liner significantly reduces the residual ridge resorption in complete denture wearers as compared to conventional denture wearers (without denture liner) over a period of 1 year.